Effect of Drama Technique on Achievement in English Reading Comprehension of Junior Secondary School Students - Law, Oluseun F. (Journal of Education in Black Sea Region, 2021)
The study examined the effect of drama technique on achievement in English reading comprehension of junior secondary school students. This study adopted the pre-test – post-test quasi-experimental design. The population of the study comprised all junior secondary school students in Ijebu-North local government, Ogun state. Two junior secondary schools were randomly selected for the purpose of the study. The students in the two schools were randomly assigned to experimental and control groups. The instrument used for data collection was the Reading Comprehension Achievement Test which has a reliability coefficient of 0.72. The experiment lasted for six weeks. The data were analyzed by Analysis of Co-Variance (ANCOVA) at a 0.05 level of significance. The results show a significant main effect of drama technique and gender on students’ achievement in reading comprehension. The results further show a significant interaction effect of drama technique and gender on students’ achievement in reading comprehension. The study recommends that teachers should adopt the use of drama techniques in teaching comprehension. Keywords: drama technique, reading comprehension, achievement in reading